Molecular Docking of Catechin from Uncaria gambir as a Potential Inhibitor of MurB Enzyme for Antibacterial Drug Development: Original/Research Article - Ilham Kurniawan (Journal of Diverse Medical Research : Medicosphere, 2026)
The increasing prevalence of antibiotic-resistant Pseudomonas aeruginosa highlights the need for novel antibacterial agents targeting essential enzymes such as MurB, a key enzyme in peptidoglycan biosynthesis. This study aimed to evaluate the inhibitory potential of catechin against MurB (PDB ID: 7ORZ) using molecular docking. Docking validation was performed through redocking of the co-crystallized ligand, yielding an RMSD of 0.962 Å, confirming the reliability of the method. Catechin exhibited a stronger binding affinity (−7.9 kcal/mol) compared to the reference ligand (−5.2 kcal/mol), with a significantly lower inhibition constant (Ki = 1.63 µM vs. 153 µM), indicating approximately 100-fold higher inhibitory potential. Interaction analysis revealed that catechin forms multiple hydrogen bonds, electrostatic interactions, and hydrophobic contacts with key catalytic residues, including Arg166, Ser239, and Glu335. These interactions suggest that catechin effectively occupies the active site and may interfere with the NADPH-dependent catalytic mechanism of MurB. In conclusion, catechin demonstrates promising potential as a MurB inhibitor and may serve as a lead compound for the development of antibacterial agents against P. aeruginosa. Further experimental validation is required to confirm its biological activity.